AN EMPIRICAL STUDY ON THE DYNAMIC RELATIONSHIP BETWEEN BIST100 INDEX AND GEPU, BOND INTEREST, EXCHANGE RATE (Third Sector Social Economic Review, 2024)
Systematic risks faced by stock investors arise from various factors, some of them are computable and some incomputable, which cannot be avoided through portfolio diversification. Many empirical studies have been conducted in the finance and capital markets literature to identify these risk factors and predict their effects on stock markets. The variables subject to studies differ and diversify according to the characteristics of different periods such as global crises, social events and pandemics. The relationship between Global Economic Political Uncertainty (GEPU), stock markets, interest rates and exchange rates has been widely studied in the economic literature, and these studies generally focus on BRICS, G7 and EU countries. In this study, the dynamic relationship between GEPU, bond interest and exchange rate variables, which are among the systematic risk factors that are thought to have an impact on the BIST 100 Index is empirically tested. ARDL bounds test approach was preferred in the study and the analyzes include the period January 2013-June 2024. According to the analysis results, it was concluded that the effect of GEPU, bond interest rates and the USD/TRL exchange rate on the BIST100 index was weak or insignificant in the short term, but in the long term, the GEPU index and bond interest rates had a negative effect on the BIST100 Index, and the USD/TRL exchange rate had a positive effect.
Keywords: BIST100 Index; GEPU; Bond Interest Rate; Exchange Rate; Systematic Risk